The Evolution of Dictionaries of Economics: from a Glossary to a - Kwary, Deny A. (HERMES - Journal of Language and Communication in Business, 2014)
Dictionaries of economics have evolved over time. In the past, most dictionaries were similar to glossaries and were in printed form. In this Internet era, some printed dictionaries have evolved into online dictionaries with various number of technological features. However, the evolution of these dictionaries has not taken into account the evolving needs and situations of the users. Consequently, as we can see from the review of the current online dictionaries of economics, these dictionaries have failed to satisfy the needs of the users, particularly the spoken text reception needs. This paper presents some principles in creating a future dictionary of economics that can satisfy the needs related to the situation when a non-native English speaker is listening to business news in the English language. The future dictionary or the proposed dictionary in this paper takes the concept of a lexicographical information system (LIS) that integrates several components into the dictionary. The four components discussed are a voice recognition function, a tooltip, an auto-summarize function, and a definition-finder. This paper shows why these four components are needed and how they can solve the users’ lexicographical problems correctly, promptly, and conveniently.